Language Assistance Services in Nonfederally Funded Safety-Net Medical Clinics in the United States (Mary Ann Liebert, 2022)
Background: In the United States, nonfederally funded safety-net clinics provide health care services to underserved populations, including patients with limited English proficiency. Unlike clinics that receive federal funding, which requires provision of qualified interpreters, these clinics are not required to provide such services. Objective: The aim of this study was to describe the types of language assistance services used by safety-net clinics and their approaches to medical interpreter training for volunteers and staff. Methods: A survey was administered by mail and email to nonfederally funded medical safety-net clinics identified from publicly available directories. The survey collected information on clinic characteristics, interpreter modalities used, and interpreter training and could be completed on paper or online. Results: Among 859 eligible clinics, 216 completed the survey (24% response rate). Few clinics reported timely access to professional interpreter services in-person (18.5%), by phone (23%), or by video (7%), while 80% of clinics used ad hoc family member or friend to interpret and 53% used ad hoc child to interpreter. Seventy-eight percent of clinics reported using bilingual staff, providers, and/or volunteers. Staff/volunteer training was provided by 22 clinics (11%). Conclusion: Most safety-net clinics relied upon ad hoc interpreters, contrary to best practices. Use of ad hoc interpreters can lead to errors in interpretation, contributing to inequities in quality of health care services. Future efforts should identify economical strategies to improve access to qualified interpreter services at nonfederally funded safety-net clinics.